Development and analysis of a flapping mechanism for biomimetic micro air vehicle / Christopher James Fearday - Christopher James , Fearday (2018)
Biomimetic micro air vehicles (BMAV) are a class of micro-sized aircraft that generate aerodynamic forces (e.g. thrust and lift) by mimicking the flapping wing motion of flying biological organisms (e.g. insects, birds, etc.). Due to the complex aerodynamics and requirements for micro-sized, ultra-lightweight components, BMAV represent a new and challenging aerospace research frontier. Very few research prototypes exist and no production models. The subject of this research is the design and testing of a new, innovative electrically powered mechanism that generates this flapping motion. In general, the small wings of insects and BMAV do not have enough surface area to generate a sufficient lift-to-weight ratio if they must rely upon conventional steady flow aerodynamics over fixed wings. Flapping the wings generates an unsteady flow in which vorticities are formed. The resulting unsteady flow field can be designed to generate much higher aerodynamic forces compared to conventional fixed wings. Rotational lift and wake capture along with the leading-edge vortex (LEV) are presently understood as the aerodynamic lift methods used most by insects. Current flapping wing vehicles make use of LEV and the more exotic clap-and-fling mechanism to produce lift. Rotational lift and wake capture are often neglected or ignored. Rotational lift is maximized by adjusting the point of pre-rotation. Experimental results show that pre-rotating the wings generates 120% more lift than allowing rotation to begin at stroke reversal. Another experiment that incorporates rotational damping increases the additional lift to 125% and extends the advance angel range over which this increased lift occurs. The mechanism used has the distinct advantage of being able to produce this optimal lift over a range of flapping frequencies without the need to tune the flapping to an optimal frequency. The novel iv utilization of the data signal processing method of cyclic averaging allows direct comparison to results obtained from dynamically scaled models in mineral oil. By adding frequency spectrum analysis, the time and frequency views provide insight into vibrational noise, types of lift and consistency of the flapping rate. Calculation of the total mass contribution of the mechanism and comparison to the lift generated shows the mechanism is useful for building a flapping wing vehicle.